2009
DOI: 10.1152/jn.91253.2008
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Information Can Influence Spatial Localization

Abstract: To localize objects relative to ourselves, we need to combine various sensory and motor signals. When these signals change abruptly, as information about eye orientation does during saccades, small differences in latency between the signals could introduce localization errors. We examine whether independent temporal information can influence such errors. We asked participants to follow a randomly jumping dot with their eyes and to point at flashes that occurred near the time they made saccades. Such flashes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 27 publications
(18 reference statements)
4
47
1
Order By: Relevance
“…In combination with evidence that shapes (Matsumiya and Uchikawa, 2001) and separations (Reeve et al, 2008) are perceived correctly for targets flashed during saccades, a parsimonious account of the findings is that temporal errors, when combining information about the flashed object's retinal location with information about eye orientation, are responsible for the observed perisaccadic mislocalization of flashed objects (see Model interpretation, below). Such a temporal explanation is also in line with our finding that temporal information can change perisaccadic mislocalization (Maij et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…In combination with evidence that shapes (Matsumiya and Uchikawa, 2001) and separations (Reeve et al, 2008) are perceived correctly for targets flashed during saccades, a parsimonious account of the findings is that temporal errors, when combining information about the flashed object's retinal location with information about eye orientation, are responsible for the observed perisaccadic mislocalization of flashed objects (see Model interpretation, below). Such a temporal explanation is also in line with our finding that temporal information can change perisaccadic mislocalization (Maij et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…The observation of a potentially close relation between synchrony perception and induced temporal shifts suggested an alternative theoretical approach, based on the model described by Maij, Brenner, and Smeets (2009). This model combines the influence of the relative temporal position of the sound on the judged temporal position of the flash (linear component) with the probability that the flash and sound are considered to arise from the same event (Gaussian component).…”
Section: Resultsmentioning
confidence: 99%
“…In analogy with saccades, it was recently shown that presenting an irrelevant tone around the time of the flash resulted in a temporal shift of the localization pattern (Maij et al 2009). To explain these results, it was suggested that the flash and the tone are optimally integrated, but only if both were presented closely enough in time.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that when flashes are presented near the time of a saccade people systematically misperceive the location of the flash (e.g., Honda 1989;Lappe et al 2000;Maij et al 2009;Mateeff 1978;Matin and Pearce 1965;Ross et al 1997;Schlag and Schlag-Rey 1995). There are, however, conflicting results regarding the effect of saccade velocity on such perisaccadic localization errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation